Serum Levels of Total Protein, Albumin and Globulin in Woman with Hyperemesis Gravidarum (Journal of Dhaka Medical College, 2010)
Background: Hyperemesis gravidarum is a severe type of vomiting in pregnancy which has significant effect on the health of mother and fetus. During this period various metabolic and endocrine changes occur in maternal body. Objectives: The present study has been designed to observe the serum total protein, albumin and globulin in women with hyperemesis gravidarum. Method: For this purpose 6o women with age ranging from 20 to 40 years were selected. The women with hyperemesis gravidarum were taken as case and Non pregnant nulliparous women & normal pregnant women during the first trimester of normal pregnancy were taken as control group. Each group consisted of 20 women. The total protein and albumin levels were measured in all study populations against the blank at wavelength of 530 nm and 620 nm in a colorimeter. Results: The serum total protein and albumin levels were significantly (p < 0.001) higher in hyperemesis gravidarum and normal pregnant women during first trimester compared to control non pregnant nulliparous women. Conclusion: Therefore the result of the present study reveals that higher levels of total protein, albumin and globulin in hyperemesis gravidarum in comparison to non pregnant nulliparous & normal pregnant women due to increase thyroid hormones and also increases thyroxine - binding globulins. Key words: Serum Total Protein; Serum Albumin; Serum Globulin; Hyperemesis Gravidarum DOI: 10.3329/jdmc.v19i1.6254 J Dhaka Med Coll. 2010; 19(1) : 58-60.